Secretory Phospholipases A2 in Plants - Mariani, Maria Elisa (2019)
Secreted phospholipases (sPLA2s) in plants are a growing group of enzymes that catalyze the hydrolysis of sn-2 glycerophospholipids to lysophospholipids and free fatty acids. Until today, around only 20 sPLA2s were reported from plants. This review discusses the newly acquired information on plant sPLA2s including molecular, biochemical, catalytic, and functional aspects. The comparative analysis also includes phylogenetic, evolutionary, and tridimensional structure. The observations with emphasis in Glycine max sPLA2 are compared with the available data reported for all plants sPLA2s and with those described for animals (mainly from pancreatic juice and venoms sources).